Sustainable competitive advantages with the debut of mobile number portability: a case of Malaysian mobile phones - Zahiruddin, Zubaidah; Zainuddin, Anizah; Mohd Yusof, Yuslina Liza (2011)
Mobile Number Portability (MNP) was implemented in December 2008 in Malaysia. MNP offers specific benefits to mobile users by allowing them to switch service providers or mobile network operators (MNO) and yet retain their existing mobile phone number. The study, therefore investigate the significant factors influencing mobile users to prefer mobile number portability (MNP). Three top Malaysia telecommunication companies (Telco) such as Maxis, Celcom and DiGi were chosen for this study. Faced with a maturing mobile telecommunication market, Telcos cannot overlook the impact MNP has over their brand loyalty. The dependent variable of this study was the competitive advantages of MNP, while the independent variables were features of MNP, loyalty, awareness, attractiveness, accessibility, social and economic factors as well as the MNP performances aspects. 519 respondents using systematic random sampling were utilized for the study. The results suggested that key features of MNP, mobile user loyalty, attractiveness of MNP package as well as the mobile users' interest on the possible economic saving through MNP as significant in influencing preferences for MNP. The managerial implications were discussed to facilitate the MNO in formulating and implementing appropriate marketing strategies to sustain competitive advantage.